The role of boundary length and adjacent patch contrast in guppy mate choice. (30th November 2020) - Sibeaux, Adélaïde; Camduras, Thomas; Endler, John A
Abstract: The presence of various combinations of adjacent colors within polymorphic species' color pattern could have a major impact on mate choice. We studied the role of pattern geometry in predicting mate choice in guppies using boundary strength analysis (BSA). BSA estimates the visual contrast intensity between two adjacent color patches ( ΔS ) weighted by the lengths of the boundaries between these adjacent color patches. We measured both the chromatic (hue and saturation) and achromatic (luminance) ΔS for each pair of adjacent patches. For each male's color pattern, we measured BSA as both mean ( mΔS ) and coefficient of variation ( cvΔS ) of all ΔS weighted by their corresponding boundary lengths. We also determined if specific color patch boundaries had an impact on female preferences and whether these predicted overall male contrast ( mΔS ). We found that males with a higher mΔS were more attractive to females and that six boundaries containing either fuzzy black or black as one of the pair colors significantly affected female preferences, indicating that 1) females favored highly conspicuous males and 2) melanin-based patches could be used as a signal amplifier, not only for orange but for other colors. Abstract : We tested if color contrast in animal patterns could affect their attractiveness to potential mates. We found that in the guppy, a species where males show a high color polymorphism, females were attracted to highly contrasted males. Moreover, the association between black patches and six different colors had an impact on females' choice. This suggests that black might be used to emphasize color signals.